2015
DOI: 10.1111/jai.12848
|View full text |Cite
|
Sign up to set email alerts
|

Processing traits of European catfish (Silurus glanis Linnaeus, 1758) from outdoor flow-through and indoor recycling aquaculture units

Abstract: The quality of fish cultured using recycling units may differ from that of fish from outdoor farming units due to a range of deviating environmental determinants. This applies not only to flesh quality but also to morphological (processing) traits. This study evaluates processing yields of sibling fish cultured in two different farming units: (i) an outdoor pond aquaculture system with a flow-through regime (24.6 AE 0.2°C ), and (ii) indoor tanks using a recirculation aquaculture system (RAS; 26.0 AE 1.0°C). C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 15 publications
1
5
0
Order By: Relevance
“…No major differences regarding the slaughtering yield occurred for the catfish originating from both environments. The obtained data fell within the limits in the literature for this species [8,19,64].…”
Section: Quantitative Flesh Productionsupporting
confidence: 87%
See 2 more Smart Citations
“…No major differences regarding the slaughtering yield occurred for the catfish originating from both environments. The obtained data fell within the limits in the literature for this species [8,19,64].…”
Section: Quantitative Flesh Productionsupporting
confidence: 87%
“…In a similar study, Jankovka et al ( 2006) [19] analysed catfishes with different origins and mentioned close values between the yields of fish from a natural environment (carcass 90.75%; torso 60.08%; and fillets 42.79%) and those that were farmed (carcass 90.76%; torso 60.86%; and fillets 45.11%).…”
Section: Quantitative Flesh Productionmentioning
confidence: 94%
See 1 more Smart Citation
“…S. glanis is particularly popular among European anglers, and its economic importance in many Central and Eastern European countries has increased because the species possesses many characteristics desirable for profitable aquaculture (e.g. its growth rate is amongst the highest of any fish, and it has tasty white boneless flesh, high carcass yield, and high feed utilization efficiency; Pruszynski and Pistelok 1999;Linhart et al 2002;Jankowska et al 2006;Adamek et al 2015). The aquaculture production of S. glanis in Europe, Asia and Africa has grown from 14 tons in 1984 to 2,026 tons in 2018.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the biogas yield of RAS sludge was higher (58% methane) compared to that of ponds (38% methane) (Nhut et al, 2019). Adamek et al (2015) investigated the flesh quality of European catfish (Silurus glanis Linnaeus, 1758) reared in two different culturing systems; RAS and outdoor farming units. It was found that skinned trunk and fillet yields, as well as deposited fat weight, were significantly higher in RAS compared to those reared in outdoor farming units thus indicating RAS a more preferable food production system for catfish.…”
mentioning
confidence: 99%